COMPARATIVE ANALYSIS OF DEVELOPMENT OF CHLAMYDOPHILA AND SALMONELLA INFECTIONS IN THE INBRED MICE DIFFERENT IN THEIR SENSITIVITES TO M.TUBERCULOSIS - D. V. Balunets; L. N. Nesterenko; Yu. S. Romanova; Yu. S. Alyapkina; N. I. Kolkova; A. S. Apt (Медицинская иммунология, 2014)
Abstract. The course of infections caused by intracellular parasitic bacteria Salmonella typhimurium and Chlamidophila pneumoniae was compared for inbred strains of mice with genetically determined susceptibity (I/St) or resistance (A/Sn) to Mycobacterium tuberculosis.Similar differences in dynamics of some common parameters (life span and pathogen numbers in affected or gans) between A/Sn and I/St mice have been revealed for tuberculosis, salmonellosis and chlamidiasis. There has been demonstrated that A/Sn animals show increased resistance to Salmonella and Chlamidia infections, as compared to I/St mice, in spite of various mechanisms of intracellular parasitism for S.typhimurium and C.Pneumoniae, and different locations of lesions induced by these bacteria in the host organism.Similar features of quite different infections at the level of macroorganism allows us to suggest that further investigation in A/Sn and I/St murine model will make it able to discover the basic features of physiolog$ical control for a lot of infections, and to reveal a genetic network that could be responsible for their favorable or adverse outcomes. (Med. Immunol., 2005, vol.7, № 5–6, pp. 583–586)